PROGRESIF SUMBER KEUANGAN ISLAM DI ERA KLASIK DAN MODERN - Asmawati Asmawati; Hamzah Hamzah (Al-Bayyinah, 2019)
The study of progressive sources of modern Islamic finance aims to look closely at the increase of Islamic financial resources in Islamic philanthropic discourse. The superiority of Islamic finance in the modern era will be able to predict the contribution of Islam to the country in the social religious field. Methodology of analysis namely by examining actual scientific sources by considering formal juridical aspects. This research proves that the progression of Islamic finance in the modern era is highly responded, it is seen from the regulation of simplification of the implementation of Islamic philanthropy; for example, zakat, waqf and BaitulMal. The response to the progression of Islamic finance is important to pay special attention toeven thoughtstill being guided by productive-based management guidelines. The great desire of Islamic finance progress in the modern era is to be able to contribute through productive movements through the coordination of independentinstitutions.